The neutrophil/lymphocyte ratio ≥3.5 is a prognostic marker in diffuse large B-cell lymphoma: a retrospective analysis from the database of the Italian regional network 'Rete Ematologica del Lazio per i Linfomi' (RELLI). Issue 14 (6th December 2019) - Annibali, Ombretta; Hohaus, Stefan; Marchesi, Francesco; Cantonetti, Maria; Di Rocco, Alice; Tomarchio, Valeria; Di Napoli, Arianna; Pelliccia, Sabrina; Battistini, Roberta; Anticoli Borza, Paola; Abruzzese, Elisabetta; Cenfra, Natalia; et al.
Abstract: In solid tumors and lymphomas, the neutrophil/lymphocyte (N/L) ratio at diagnosis has been shown to be a prognostic factor. The aim of our study was to validate the originally reported N/L ratio cut-point of 3.5 in patients with diffuse large B-cell lymphoma (DLBCL) registered in an Italian real-life database. The prognostic role of the N/L ratio at diagnosis on event-free survival (EFS) and overall survival (OS) was assessed in 505 patients with DLBCL. Patients with an N/L ratio <3.5 ( n  = 249) had a 4-year EFS probability of 76% and OS probability of 86%, significantly higher than the 4 year EFS rate of 48% and OS rate of 64% in patients with N/L ratio ≥3.5 ( n  = 256, both p <.0001). The N/L ratio was an independent prognostic factor in the multivariate analysis including the IPI score, and could separate patients with a low/intermediate risk IPI (IPI <3).